2013
DOI: 10.1039/c3dt50371b
|View full text |Cite
|
Sign up to set email alerts
|

Potentially cytotoxic new copper(ii) hydrazone complexes: synthesis, crystal structure and biological properties

Abstract: A new set of penta-coordinated copper(II) hydrazone complexes containing solvated methanol were synthesized by reacting the hydrazone ligands, 2-acetylpyridine benzoyl hydrazone (HL1) and 2-acetylpyridine thiophene-2-carboxylic acid hydrazone (HL2), with [CuCl2(DMSO)2] and characterized by different spectral methods. Single crystal X-ray diffraction studies of the complexes revealed that both of them, [CuCl(L1)(MeOH)] (1) and [CuCl(L2)(MeOH)] (2), have square pyramidal geometry around the cupric ion, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(83 citation statements)
references
References 49 publications
3
79
0
1
Order By: Relevance
“…These complexes show oxidase biometric catalytic activity, anticancer and antimicrobial activities [6][7][8][9][10][11]. The study of Schiff bases and their complexes has become a focal point of interest for chemists in recent years, not only for their several structural features, but due to their potential application in various fields [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These complexes show oxidase biometric catalytic activity, anticancer and antimicrobial activities [6][7][8][9][10][11]. The study of Schiff bases and their complexes has become a focal point of interest for chemists in recent years, not only for their several structural features, but due to their potential application in various fields [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…17 There is no obvious charge delocalization in the molecules, as evidenced by the typical C-N single bonds between atoms C8 and N3. Symmetry codes: (1) and Cg (2) are the centroids of C1-C2-C3-C4-C5-C6 (1) and C1-C2-C3-C4-C5-C6 (3), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cg (1) and Cg (2) are the centroids of N3-C11-C10-C9-C13-C12 and C1-C6 of 1; Cg(3), Cg (4),Cg (5)and Cg (6) are the centroids of N3-C11-C10-C9-C13-C12, C1-C6, N6-C24-C23-C22-C26-C25, and C14-C19 of 2.…”
Section: Structure Description Of the Compoundsmentioning
confidence: 99%
“…It can react with aldehydes to form isonicotinohydrazones, which show interesting biological activities [1][2][3][4]. Moreover, isonicotinohydrazone compounds usually possess three or more donor atoms, which can readily form complexes with various metal atoms [5][6][7][8][9][10][11][12]. Recently, we found that halido-substituted hydrazones have potential antimicrobial activities [13].…”
Section: Introductionmentioning
confidence: 99%